Efektivitas Penambahan Nanokitosan dalam Pakan Terhadap Kelangsungan Hidup dan Pertumbuhanan Ikan Nila (Oreochromis niloticus) - Miska Sanda Lembang; Reni Tri Cahyani; Christine Dyta Nugraeni (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
Tilapia cultivation in Tarakan City is one of the sources of community livelihood. However, environmental problems cause fish to be susceptible to diseases caused by bacteria in the waters. This study aims to increase the potential of chitosan with nanoparticle size, which is added to feed for the survival and growth of tilapia seed. Nanochitosan is an extract from crab or shrimp shell waste, which functions as an immunostimulant. By utilizing the active nature of the nanoparticle size, it can provide better growth and survival of tilapia seed. The research was conducted with an experimental method of two treatments and three replications. One treatment was without the addition of nanochitosan and the second treatment was with the addition of nanochitosan in the feed. The results of the synthesis of nanochitosan obtained size based on the amount with the highest intensity at 537.17 nm. Water quality were still optimal, namely the temperature was 27-29°C and the pH was between 7.3-7.8. The dissolved oxygen content (DO) obtained in the two treatments was 1.3-5.8 mg/L. The range of ammonia levels in the two treatments was 0.1-3.5 mg/L. Based on the results of the study, it was found that the treatment using chitosan nanoparticles in the feed was more effective than without using chitosan nanoparticles in the feed on the growth and survival of Tilapia Seeds. The results of the T test showed that the daily specific growth rate (SGR) in all treatments was not significantly different (P>0.05), but the survival rate (SR) of tilapia seed in all treatments was significantly different (P<0.05). These results can be concluded that the addition of nanochitosan in feed has a significant effect on increasing the survival of tilapia seed.